HOW ORAL CORRECTIVE FEEDBACK IS PERCEIVED BY EFL BILINGUAL ELEMENTARY SCHOOL TEACHER - Novia Mustika Dewi; Ainun Putri Nurdiya; Mitha Mediana Sukandar; Lucky Rahayu Nurjamin (IPI Garut Press, 2023)
Oral corrective feedback (OCF) is one of the important teaching methods because it can aid the students in the learning process. The EFL teacher in bilingual primary schools was studied for this research because they are still in under research. This study tries to find out how oral corrective feedback (OCF) is perceived by EFL bilingual primary school teachers. This study used case study. The data were collected using semi-structured interview with one of the teacher. The findings of this research, there are four kinds of oral corrective feedback (OCF) that used often by the teacher in the learning process that are, recast, repetition, elicitation and paralinguistic signals and the mechanism used bases on the situations individually or group correction. The second findings of this research is from the teacher perspective giving oral corrective feedback (OCF) can be easier for students to remember the correction from the teacher